MULTIMEDIA VOSITALARI ASOSIDA TALABALARNI MADANIYATLARARO KOMMUNIKATIV KOMPETENSIYALARINI RIVOJLANTIRISH TEXNOLOGIYALARI - Tleumuratova, A.B. (SCIENCE and SOCIETY, 2023)
This article describes the technologies for the development of intercultural communicative competence of students based on multimedia, methods for achieving effective results through their use in the learning environment.